2003
DOI: 10.1046/j.1365-2672.2003.01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the inactivation of bacterial spores by reciprocal pressurization treatment

Abstract: Aims: The mechanism of the inactivation of Bacillus subtilis spores by reciprocal pressurization (RP) was unclear. Therefore, the mechanism was investigated. Methods and Results: To investigate the effects of RP and continuous pressurization (CP) treatments on the inactivation and injury of B. subtilis spores, spores were treated at 25, 35, 45 and 55°C under 200, 300 and 400 MPa. RP treatment was effective in injuring and inactivating spores. Scanning electron microscopy and transmission electron microscopy ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Initiation of B. subtilis spores germination was achieved with static pressures between 200 and 400 MPa (Furukawa et al, 2003). It also has been shown that treatment with pressurized CO 2 helps induce spore germination, rendering the spores more susceptible to deactivation (Ballestra and Cuq, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Initiation of B. subtilis spores germination was achieved with static pressures between 200 and 400 MPa (Furukawa et al, 2003). It also has been shown that treatment with pressurized CO 2 helps induce spore germination, rendering the spores more susceptible to deactivation (Ballestra and Cuq, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals including pesticide should not be used for this purpose because they have been recognized as environmental pollutants. Application of critical CO, (Spilimbergo et al, 2003), hydrostatic pressures (Hauben et al, 1997;Furukawa et al, 2003), hydroxyl radicals (Bai et al, 2005), and shock pressures (Abe et al, 2005) seem to be available for use to kill the harmful marine microorganisms in ships' ballast water. l n this study, we examined the lethality of shock pressures to the Vibrio sp.…”
mentioning
confidence: 99%
“…We have indicated that repeated pressure treatment (repeated compression, pressurization and decompression) was effective to inactivate bacterial spores (Furukawa et al, 2000a;Furukawa et al, 2000b;Furukawa et al, 2003). Spores were more inactivated by RP treatment than by continuous pressure treatment (consisting of 1 cycle of 30 min pressurization; CP treatment).…”
mentioning
confidence: 99%
“…Germinated spores were increasingly injured by the repeated decompression. In RP treatment, spores were first germinated and then were injured by repeated decompression (Furukawa et al, 2000a;Furukawa et al, 2000b;Furukawa et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation